Experimental investigation of the effect of air velocity on a unit cooler under frosting condition: a case study - Bayrak, Ergin; Caglayan, Akin; Konukman, Alp Er Şevki (Springer, 2017)
Finned tube evaporators are used in a wide range of applications such as commercial and industrial cold/freezed storage rooms with high traffic loading under frosting conditions. In this case study, an evaporator with an integrated fan was manufactured and tested under frosting conditions by only changing the air flow rate in an ambient balanced type test laboratory compared to testing in a wind tunnel with a more uniform flow distribution in order to detect the effect of air flow rate on frosting. During the test, operation was performed separately based on three different air flow rates. The parameters concerning test operation such as the changes of air temperature, air relative humidity, surface temperature, air-side pressure drop and refrigerant side capacity etc. were followed in detail for each air flow rate. At the same time, digital images were captured in front of the evaporator; thus, frost thicknesses and blockage ratios at the course of fan stall were determined by using an image-processing technique. Consequently, the test and visual results showed that the trendline of air-side pressure drop increased slowly at the first stage of test operations, then increased linearly up to a top point and then the linearity was disrupted instantly. This point speculated the beginning of defrost operation for each case. In addition, despite detecting a velocity that needs to be avoided, a test applied at minimum air velocity is superior to providing minimum capacity in terms of loss of capacity during test operations.
Keywords: Performance